Trajectories of activities of daily living according to dementia among middle-aged and older people in South Korea: a longitudinal study from 2006 to 2020 (14 years) - Chae, Soo Eun (Frontiers in Psychiatry, 2024)
This study investigates the patterns of change in Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) among older adults in South Korea. Furthermore, it explores how these patterns differ by dementia status. Data from the Korea Longitudinal Study of Ageing (KLoSA) spanning from 2006 to 2022 were analyzed, encompassing a cohort of Nondementia condition group (including mild cognitive impairment, N=6004+38) and dementia group (N=91), aged 45 and older (born before 1961). Using Latent Growth Curve Models, we examined the developmental trajectories of ADL and IADL for the entire sample, revealing a linear decline in both as individuals aged. Notably, IADL scores exhibited a more discrepancy between dementia conditions compared to ADL scores (the broader range of IADL scores (0-10) compared to ADL scores (0-7)), highlighting dementia sensitivity to sociocultural factors (reflected in IADL). Those with dementia consistently showed lower ADL and IADL scores compared to non-dementia individuals (those without a dementia diagnosis maintained a score of 0). Additionally, the variance in scores increased with age among the dementia group, indicating worsening daily life performance and greater individual variation (F=226.630, p<.001). The research results suggest that dementia is influenced not only by simple self-regulation function but also by social and cultural functions related to daily living performance (as reflected in IADL).